Attention modulates saccadic inhibition magnitude. Issue 6 (June 2013) - Buonocore, Antimo; McIntosh, Robert D.
Visual transient events during ongoing eye movement tasks inhibit saccades within a precise temporal window, spanning from around 60–120 ms after the event, having maximum effect at around 90 ms. It is not yet clear to what extent this saccadic inhibition phenomenon can be modulated by attention. We studied the saccadic inhibition induced by a bright flash above or below fixation, during the preparation of a saccade to a lateralized target, under two attentional manipulations. Experiment 1 demonstrated that exogenous precueing of a distractor's location reduced saccadic inhibition, consistent with inhibition of return . Experiment 2 manipulated the relative likelihood that a distractor would be presented above or below fixation. Saccadic inhibition magnitude was relatively reduced for distractors at the more likely location, implying that observers can endogenously suppress interference from specific locations within an oculomotor map. We discuss the implications of these results for models of saccade target selection in the superior colliculus.